A study on length measurement method of hot large forgings based on binocular vision system. (August 2022) - Wang, Bangguo
Highlights: The length of hot large forging is measured based on binocular vision system. The edge points are obtained by curve fitting the projection points on the fitting plane. The relative error of the dimension measuring system in measuring the length of forgings can reach 0.547%. Abstract: A length measurement method of hot large forgings is proposed in this paper. Firstly, the images of hot forgings are acquired by two monochrome Charge Coupled Device (CCD) cameras, and the light strips are detected according to the characteristics that the value of the pixels in the vertical direction of the light strips is approximate the Gaussian distribution. Secondly, the sub-pixel centers of each light strips in the left and right images are calculated and used for matching and three-dimensional (3D). Finally, the curve represented by quintic polynomial is employed to fit the two-dimensional (2D) points which are projected by 3D points on the fitted plane, and the edge of the forging is calculated by the curvature of the fitted curve. The experimental results in laboratory show that the measurement accuracy can reach 0.547%. The length measurement time of hot forging is 3.7 s.